Replacement of the ascending aorta and aortic valve for annuloaortic ectasia with Carbomedics Carbo-Seal valsalva™ graft: mid- to long-term results - Cavolli, Raif; Kahraman, Dogan (Frontiers in Surgery, 2026)
PurposeThe modified Bentall procedure utilizing the Carbomedics Carbo-Seal Valsalva™ graft can be employed to address aortic root pathologies. In this study, we examined the performance of this conduit specifically for treating isolated annuloaortic ectasia. Our objective was to evaluate the long-term outcomes of these surgeries.MethodsA total of 48 consecutive patients with annuloaortic ectasia underwent aortic root replacement using the Carbomedics Carbo-seal Valsalva™ graft between 2012 and 2024. In 7 patients, additional cardiac procedures were performed: two underwent mitral valve annuloplasty, and five had coronary artery bypass grafting. The mean cardiopulmonary bypass time and aortic clamp time during the modified button-Bentall operations were 151 ± 37 min and 128 ± 14 min, respectively.ResultsThe operative mortality rate was 2.1% (n = 1). Late mortality was 6.3% (n = 3), with causes including chronic heart failure (2.1%; n = 1), cerebral hemorrhage (2.1%; n = 1), and pulmonary complications (2.1%; n = 1). Major late complications included cerebral hemorrhage (4.2%; n = 2), pulmonary bleeding (2.1%; n = 1), and gastrointestinal hemorrhage (2.1%; n = 1). The Kaplan–Meier estimated survival rates were 96.22% at 5 years and 95.20% at 10 years. Additionally, the Kaplan–Meier curves showed event-free survival rates of 98% at 5 years and 82% at 12 years (95% CI).ConclusionsModified button-Bentall operations for annuloaortic ectasia, with Carbomedics Carbo-Seal Valsalva™ graft, can be performed with a low mid- and long-term mortality and morbidity.